Mapping Oilseed Market Integration and Trade Causality: A Focus on Tamil Nadu and India's Interstate Dynamics - Malaisamy, A.; Shankar, Gowri (Current Research Progress in Agricultural Sciences Vol. 6, 2024)
India has been grappling with a chronic shortage of edible oils due to insufficient domestic oilseed crop production, even though it briefly achieved self-sufficiency during the “Yellow Revolution” in the early 1990s. Oilseed crops like Sesame and Groundnut experience significant price fluctuations due to factors like seasonal production patterns, their perishable nature, and the risk involved in the production and marketing of output. The farmers are further complicated by a lack of information about market conditions, including the timing of arrivals and prices. Market integration, which helps stabilize prices and improve the efficiency of the marketing system. This study focuses on analysing the market integration of major oilseed crops such as Sesame, and Groundnut in India from January 2013 to January 2024. Johansen's cointegration test and Granger Causality test were applied to examine how prices in different markets influence one another. The stationarity of the prices was tested using the Augmented Dickey-Fuller test. The results confirmed that the prices are cointegrated, showing a strong interdependence between them. The analysis also revealed causal relationships between regions, such as bidirectional causality in the case of Sesame and Groundnut. The findings underscore the importance of further research to address production challenges, improve technical methods, and develop informed policies to manage the issues faced by oilseed crop-growing farmers. This will help overcome obstacles in production and ensure a more efficient marketing system. The study recommended that a meticulous study on constraints that obstruct the production process can help in understanding the problems and bringing the new technology. There is a need to address new challenges that transcend the traditional decision-making horizons of producers, consumers and policymakers.